Microstructure and Mechanical Properties Evolution of P235GH TC1 Steel Fire Tubes from a Fire-Tube Boiler with 14 Tons Capacity and 13 Bars Pressure - Peeratatsuwan, Chaiyawat; Ariyakul, Yossiri; Sangsawang, Chatnugrob; Sukprasertchai, S.; Chowwanonthapunya, Thee (My University, 2026)
Comprehensive understanding of the microstructural degeneration and mechanical property degradation is of great importance to evaluate the reliability of used boiler tubes. This study describes the microstructural and mechanical evolution of P 235GH TC1 steel fire tubes which had been used in a fire-tube boiler for 3, 5, and 20 years. The investigation includes visual inspection, dimensional examination, chemical composition analysis, microstructural studies, scanning electron microscopy equipped with energy-dispersive x-ray spectroscopy (SEM-EDX), x-Ray diffraction (XRD), and tensile tests. Results reveal that prolonged exposure to the actual fire boiler environment induced the high temperature and oxidizing atmosphere. This atmosphere facilitated the diffusion and oxidation of carbon and manganese, leading to the depletion of both elements in the aged tubes. The carbon and manganese depletion and the influences of thermal exposure stimulated pearlite decomposition, resulting in the formation of a ferrite-dominated microstructure. The presence of ferrite-dominated microstructure and the deterioration of the solid solution effect due to the carbon and manganese depletion caused a reduction of mechanical performance and plastic deformation resistance of aged tube. The microstructural evolution and mechanical property evaluation indicate the significance of additional microstructural investigation techniques, such as replica examination. This useful method should be included in the routine inspection of the age fire tubes, particularly for those in the prolonged service stage. The addition of this method can improve the reliability of regular inspections, especially for aged fire-tube boilers.
Keywords: Fire-tube boiler; Mechanical properties; Microstructure; P 235GH TC1 steel